Plot Concept Analysis of Montgomery’s Novel - Safnidar Siahaan (English Department, University of Riau Kepulauan, Batam,Indonesia, 2017)
This study analyzed one of the intrinsic elements in the novel entitled Anne of Green Gables written by Lucy M. Montgomery. To analyze this novel, the researcher used the theory of Nurgiyantoro (1995) especially analyzing the novel plot. It was used to get more understanding the plot of the Anne of Green Gables novel. Plot, or storyline, was often listed as one of the fundamental elements of fiction. It was the rendering and ordering of the events and actions of a story. In this research, plot will be divided into three those are; a beginning, middle, and an ending.